International Evidence Based Reappraisal of Genes Associated With Arrhythmogenic Right Ventricular Cardiomyopathy Using the Clinical Genome Resource Framework. (June 2021) - James, Cynthia A.; Jongbloed, Jan D.H.; Hershberger, Ray E.; Morales, Ana; Judge, Daniel P.; Syrris, Petros; Pilichou, Kalliopi; Domingo, Argelia Medeiros; Murray, Brittney; Cadrin-Tourigny, Julia; Lekanne Deprez, Ronald; Celeghin, Rudy; et al.
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited disease characterized by ventricular arrhythmias and progressive ventricular dysfunction. Genetic testing is recommended, and a pathogenic variant in an ARVC-associated gene is a major criterion for diagnosis according to the 2010 Task Force Criteria. As incorrect attribution of a gene to ARVC can contribute to misdiagnosis, we assembled an international multidisciplinary ARVC Clinical Genome Resource Gene Curation Expert Panel to reappraise all reported ARVC genes. Methods: Following a comprehensive literature search, six 2-member teams conducted blinded independent curation of reported ARVC genes using the semiquantitative Clinical Genome Resource framework. Results: Of 26 reported ARVC genes, only 6 ( PKP2, DSP, DSG2, DSC2, JUP, and TMEM43 ) had strong evidence and were classified as definitive for ARVC causation. There was moderate evidence for 2 genes, DES and PLN . The remaining 18 genes had limited or no evidence. RYR2 was refuted as an ARVC gene since clinical data and model systems exhibited a catecholaminergic polymorphic ventricular tachycardia phenotype. In ClinVar, only 5 pathogenic/likely pathogenic variants (1.1%) in limited evidence genes had been reported in ARVC cases in contrast to 450 desmosome gene variants (97.4%). Conclusions: Using the Clinical Genome Resource approach to gene-disease curation, only 8 genes ( PKP2, DSP, DSG2, DSC2, JUP, TMEM43, PLN, and DES ) had definitive or moderate evidence for ARVC, and these genes accounted for nearly all pathogenic/likely pathogenic ARVC variants in ClinVar. Therefore, only pathogenic/likely pathogenic variants in these 8 genes should yield a major criterion for ARVC diagnosis. Pathogenic/likely pathogenic variants identified in other genes in a patient should prompt further phenotyping as variants in many of these genes are associated with other cardiovascular conditions. Abstract : Supplemental Digital Content is available in the text.